Article Coaching Clinic dalam Peningkatan Kapasitas Publikasi Ilmiah Dosen di Universitas Hamzanwadi - Khirjan Nahdi; Sitti Rohmi Djalilah; Shahibul Ahyan; Samsul Lutfi; Danang Prio Utomo (Indonesian Institute For Counseling, Education and Therapy, 2020)
Community Service entitled Article Coaching Clinic in Increasing the Capacity of Scientific Publications for Lecturers at Hamzanwadi University aims to improve the skills of lecturers in compiling scientific publications so that writing habits are created as an academic culture at Hamzanwadi University. This activity is carried out using the workshop method and online mentoring in accordance with the development of the articles on the results of the article clinic activities. Of the 114 articles that were submitted to this clinic, 108 of them were successfully submitted, and 85 of them were published. It was concluded that coaching clinic activities in encouraging the number of scientific publications were very strategic because the material was adapted to the needs of the journal. Furthermore, the activity continues by monitoring the progress of writing, until the article is declared ready to be submitted.